Factors influencing human-elephant conflict intensity: an assessment in the Bia Conservation Area, Ghana - Lavelle, Jessica (My University, 2011)
Human-elephant conflict (HEC) occurs across Africa and is a major threat to the continued existence of the African elephant. To effectively implement mitigation measures, a thorough understanding of the spatial and temporal patterns of HEC is required. This study used a systematic, grid-based geographical information system (GIS) to analyse the spatial and temporal relations of HEC intensity in 2004 and 2008 with underlying environmental variables in a forest habitat, the Bia Conservation Area (BCA), Ghana. Relationships between crop-raiding incident data, Moderate Image Resolution Spectroradiometer (MODIS) Enhanced Vegetation Index (EVI) values and remotely sensed derived data were investigated at a 10 km2 scale using principal components analysis (PCA) and correlation analysis. Crop-raiding was found to be clustered into distinct areas. The onset of crop-raiding in 2004 and 2008 can be attributed to seasonal variation in vegetation biomass. Decreases in EVI values were matched with crop-raiding incidents. The high number of crop-raiding incidents in 2004 could be attributed to the large fluctuations in vegetation biomass in comparison to 2008. HEC intensity was not significantly related to the environmental variables analysed at the 10 km2 scale. These results suggest that HEC intensity may be influenced by vegetation quality, soil mineral content and/or human density. A grid-based GIS system with a 10 km2 resolution used in combination with remotely sensed data and statistical tools is useful for identifying spatial patterns of HEC, even with relatively small incident data sets. The methods used in this study could be applied to other forest habitats experiencing HEC for comparative analysis. The influence of vegetation quality, soil mineral content and human density on HEC intensity in forest habitats requires further analysis.
Keywords: human-elephant conflict; EVI; crop-raiding